DESIGN PHASE OF A CYLINDRICAL LONG-SPAN COAL SHED WITH STEEL ARCH SPACE-TRUSS STRUCTURE - Angga Fajar Setiawan; Akhmad Aminullah; Ali Awaludin; K. T. N. Gherry; Y. A. Adhitama; M. Fauzi Darmawan (Prodi Teknik Sipil Fakultas Teknik Universitas Sebelas Maret Surakarta, 2022)
This paper discusses the structural design phase of a long-span coal shed structure in a 2x50 MW steam power plant. This study aims to share knowledge on how to design a long-span coal shed structure safely based on the design standards. The main structural system of the coal shed roof is a steel arch space-truss with 120 m of span and 31 m of height above supporting 12.5 m height of reinforced concrete columns. The superstructure contains a roof system and reinforced concrete system. The substructure system consists of a tie beam, pile cap, and bore pile. In the numerical model, all structural members were idealized as frame elements, except the pile cap that to be idealized as shell elements. Then, the soil springs were assigned to the bore pile element nodals with a 1 m interval to simulate the soil-structure interaction. The gravity loads due to dead loads, additional dead loads, live loads, rain loads, and lateral loads due to wind action and earthquakes to be considered. Furthermore, the structural analysis was conducted with non-linear geometric to simulate the large displacement effects and tension only element of the wind bracing. In addition, a simplified method to estimate the structural stability under lateral load was conducted. Based on the structural analysis and structural design, the coal shed structure could fulfill the safety criteria in terms of ultimate and serviceability limit based on the design code criteria. Furthermore, the non-linear geometry and stability issue should be considered with an appropriate structural analysis method.